Implementation of the Leadership Management Process of Islamic Educational Institutions in Internalizing Religious Moderation in Indonesia - Slamet Riyadi; Achmad Abdul Azis; Arkam Lahiya; Bashori Bashori; Al Munip Al Munip (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2023)
This study aims to describe the implementation of the leadership management process in Islamic educational institutions in Indonesia. This research uses a literature study or literature approach with a qualitative descriptive approach. The results of the study concluded that the implementation of the leadership management process of Islamic educational institutions in the internalization of religious moderation in Indonesia includes efforts to create harmony and create mutual respect for each other's beliefs, by looking at the function of religious moderation itself and the goals and objectives to be achieved. The implementation of the leadership management process of Islamic educational institutions in internalizing religious moderation in Indonesia includes efforts to create harmony and create a sense of mutual respect for each other's beliefs, by looking at the function of religious moderation itself and the goals and objectives to be achieved. Thus, an educator's strategy is created in carrying out and delivering learning material through the insertion of relevant learning material with moderation, it is necessary to optimize the learning approach so that it fosters a critical mindset with mutual respect for differences in all things, being tolerant and democratic, being able to express think with an idea, have an attitude of sportsmanship and a high sense of responsibility, besides that it is also necessary to organize programs, conduct training and special provision related to religious moderation and fulfillment in achieving evaluation aspects.Keyword: Leadership Management; Islamic Educational Institutions; Internalization of Religious Moderation.